2021
DOI: 10.3390/nu13124323
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Behaviors, Health Literacy, and Health Locus of Control of Secondary Schoolers in Southern Poland: A Cross-Sectional Study

Abstract: Nutritional behaviors remain an essential part of a healthy lifestyle. It seems obvious that unfavorable health behaviors adopted in adolescence are maintained late in adulthood and may have a profound effect on health status. The main aim of this study was to assess the association between nutritional behaviors and health literacy (HL), health locus of control (HLC), and socioeconomic variables in secondary school pupils from a voivodship (the main unit of territorial division) in southern Poland. The analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
(69 reference statements)
1
3
0
1
Order By: Relevance
“…On the contrary, it seems that a high level of external HLC observed in subjects with overweight conditions or obesity, especially in women, may be associated with higher susceptibility to stress [ 19 ] and this may cause emotional eating [ 31 ]. Recent studies by Duplaga et al [ 32 ] showed that the scores of secondary school adolescents with higher external HLC with the impact of others show that they are more likely to consume fast food, which supports our findings. An external HLC with the impact of others in participants with obesity seems to have a negative effect on changing lifestyle and lead to constant seeking for a “proper” physician.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, it seems that a high level of external HLC observed in subjects with overweight conditions or obesity, especially in women, may be associated with higher susceptibility to stress [ 19 ] and this may cause emotional eating [ 31 ]. Recent studies by Duplaga et al [ 32 ] showed that the scores of secondary school adolescents with higher external HLC with the impact of others show that they are more likely to consume fast food, which supports our findings. An external HLC with the impact of others in participants with obesity seems to have a negative effect on changing lifestyle and lead to constant seeking for a “proper” physician.…”
Section: Discussionsupporting
confidence: 92%
“…dos participantes e a prejudicar os estudos de 24% 40 . Ademais, o uso intenso do computador foi relacionado com comportamentos nutricionais menos benéficos, uma alta prevalência de sintomas mentais e musculoesqueléticos entre estudantes, mais prevalentes entre alunos do quarto ano, em comparação com os do segundo ano 24,29,41 .…”
Section: Resultsunclassified
“…The study has been developed in Spain, but it can be observed that the message conveyed by the influencer is slowly reaching international markets. This may be because the real food trend covers a hot topic in many Western countries, mainly the health problems associated with a change in diet towards more ultra-processed food [ 38 , 39 , 40 , 41 , 42 ]. Most of the time, the information shared by different bodies is confusing and even contradictory, which brings about confusion among consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these results, we encourage companies to listen to both the influencers and followers, include and give them active roles in the design of their products, and create solutions for this group of consumers, which is growing exponentially, especially among young people [ 41 ]. Therefore, a wide range of possibilities exist for companies to listen to food-related trends online and design suitable alternatives for them.…”
Section: Discussionmentioning
confidence: 99%